IPSID- a Neglected Cause of Chronic Diarrhea - Miah, Md Rubel; Imam, Syed Ali; Akter, Sultana; Khan, Ejrarul Alam; Mallik, Md Uzzwal; Kabir, AKM Humayon; Biswas, Sarmistha; Kabir, Md Asadul; Sardar, Md Hafiz (Journal of Medicine, 2022)
immunoproliferative small intestinal disease is considered as a rare condition and has endemicity inMediterranean countries and often associated with campylobacter jejuni infection. This conditionvaries in severity from benign to frankly malignant. Prolonged remission can be obtained with longterm antibiotic therapy but chemotherapy is required for those who have aggressive disease. Bangladeshidata on IPSID is sparse. Here our patient 21 years old male presented with chronic diarrhoea, occasionalvomiting, severe weakness and significant unintentional weight loss. He had cachectic body built,bipedal edema, easy bruising, glossitis with angular stomatitis. His upper GI endoscopy showed multiplenodular lesion in the duodenum. Biopsy was taken from nodular lesion and sent for histopathology,geneXpert and culture. Histopathology revealed IPSID. He was treated with tetracycline and improvedclinically. J MEDICINE 2022; 23: 84-86